Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
5 * log ( 6 / 11 ) = 5 * ( log6 - log11 ) = 5 * [ log(2 * 3) - log11] = 5 * (log2 + log3 - log11 ).
We know that C log a = log a^C.
We know that log (x/y) = log x - log y
We know that log xy = log x + log y
Therefore... log(6/11)^5 =
5 * log (6/11). Which can be expanded to...
5 (log 6 - log 11) ... 5 (log 3 + log 2 - log 11)
Its a law of logarithms.
We know that log (x/y) = log x - log y
We know that log xy = log x + log y
Therefore... log(6/11)^5 =
5 * log (6/11). Which can be expanded to...
5 (log 6 - log 11) ... 5 (log 3 + log 2 - log 11)
Its a law of logarithms.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.